Pengaruh Manajemen Laba, Umur Perusahaan dan Leverage Terhadap Tax Avoidance - Nur Indah Permatasari (Universitas Muhammadiyah Metro, 2019)
The main objective in this study is to determine whether earnings management, company age has a positive effect on tax avoidance and leverage has a negative effect on tax avoidance. The type of data used is secondary data. This study uses secondary data obtained from annual reports of manufacturing companies that have been on the Stock Exchange during 2014-2017. The sampling method used was puposive sampling. Data were analyzed using SPSS version 21. The results showed that earnings management had a positive effect on tax avoidance. While the company's age and leverage have no effect on tax avoidance.